The Significance of the "Ransom Saying" in Mark 10:45 - Reid, Duncan 1950- (2022)
The ransom saying in Mark 10:45 has been variously understood as referring to Jesus's death as a substitutionary sacrifice for the forgiveness of sins, a victory over demonic forces, or an exemplary sacrifice for his followers. This study assesses the relative plausibility of these three interpretations within the broader context of Mark's Gospel. A survey of the primary proposed textual allusions behind the saying and a consideration of the possible meanings of λύτρον ἀντί in light of ancient Greek texts indicate that all three readings are possible. In the broader literary context of Mark, however, the evidence does not support reading the ransom saying as a reference to Jesus's death as a sacrifice for sins or a means of victory over demonic powers. Instead it favors reading the saying as a reference to Jesus's death as an exemplary sacrifice for his followers.
Keywords: Christus Victor; Jesus's death; Mark; Ransom; Substitution